KOMPOSISI MAKROBENTOS DI PADANG LAMUN PULAU PARI, KEPULAUAN SERIBU, JAKARTA - Subandi, Riyana; Hadiyanto; Ramdhan Firdaus, Mochamad; Reza Cordova, Muhammad (Universitas Cokroaminoto Palopo, 2025)
Seagrass ecosystems play a crucial role as feeding grounds, spawning sites, and refugia for various marine organisms, including macrozoobenthic communities. Macrozoobenthos are ecologically significant in energy cycling, organic matter decomposition, and serve as bioindicators for assessing environmental quality. This study aimed to analyze the composition, dominance, and diversity of macrozoobenthos in the seagrass beds of Pari Island and to evaluate their implications for coastal ecosystem management. Samples were collected from 27 research plots in the seagrass meadows of Pari Island between September and November 2021 using a hand corer to a depth of 10–15 cm. Sediment samples were sieved, the macrozoobenthic organisms were sorted, identified, and grouped into five major taxa: Polychaeta, Crustacea, Mollusca, Echinodermata, and other minor phyla. Community structure was assessed by calculating absolute abundance, relative abundance, as well as ecological indices including the Shannon–Wiener diversity index, Pielou’s evenness, and Simpson’s dominance index. A total of 2,386 individuals were recorded, consisting of Polychaeta (73.7%), Crustacea (13.7%), minor phyla (11.8%), Echinodermata (0.5%), and Mollusca (0.3%). The diversity index ranged from 0.92 to 1.49, evenness from 0.48 to 0.80, and Simpson’s dominance index (C) from 0.44 to 0.69. These results indicate that Polychaeta dominated nearly all sampling stations, whereas other taxa were only sporadically present. The macrozoobenthic community structure in Pari Island reflects low to moderate diversity, with uneven distribution among taxa. The findings highlight the ecological importance of seagrass beds as primary habitats for benthic infauna, while also demonstrating their vulnerability to anthropogenic pressures. Consequently, this study provides a scientific basis to support seagrass conservation, benthic bioindicator-based monitoring, and sustainable coastal management in the Kepulauan Seribu region.